E-070 Treatment of symptomatic intracranial arterial stenosis with balloon-expandable sirolimus-eluting stents: safety, efficacy, and long-term clinical follow-up. (4th July 2012) - Gottumukkala, R; Kadkhodayan, Y; Mazumdar, A; Moran, C; Derdeyn, C; Cross, D
Abstract : Purpose: Intracranial arterial stenosis is one cause of ischemic stroke. A two-step procedure using one specific angioplasty balloon (Gateway®) and one specific self-expanding stent (Wingspan®) was inferior to best medical management in a recent trial (SAMMPRIS), partly due to a greater than expected complication rate in its interventional arm. There are other devices that can be used to dilate stenotic cerebral arteries in a one-step approach. If complications are fewer and long-term results are favorable, treatment by dilation with such devices may achieve superiority over best medical management in patients who are medically refractory. Drug-eluting balloon-mounted stents (DES) can be deployed in a one-stage procedure in stenotic intracranial arteries and are less prone to re-stenosis than bare-metal stents, though there is some concern about late in-stent thrombosis. Long-term outcomes of intracranial DES treatment have not been previously studied. We report the long-term follow-up of 10 patients treated with DES for symptomatic intracranial arterial stenosis refractory to medical management. Methods: From 2003 to 2007, 10 patients (mean age, 58.9 years) with intracranial arterial stenosis that remained symptomatic (recurrent TIA or stroke) despite medical therapy were treated with DES. Twelve Cipher balloon-expandable stents were deployed, with 2 of the 10 patients receiving two stents each due to the presence of multiple high-grade lesions. Four lesions required pre-dilation with balloon angioplasty using the Maverick® system. Medical records were reviewed for demographic information, procedural details, complications, and follow-up imaging results. Telephone interviews were performed in August, 2011, to assess for new stroke or TIA, disability according to the modified Rankin Scale (mRS), and compliance with anti-platelet medications. Results: Stenotic lesions were located in the internal carotid artery in six patients, the middle cerebral artery in one patient, the vertebral artery in two patients, and both a vertebral artery and the basilar artery in one patient. All 12 stents were successfully deployed. A mean stenosis of 81.5±13.3% was reduced to 7.1±16.3%. In 1 patient with 99% stenosis of the left ICA, the lesion could not be reduced to <55% stenosis. There were no procedural complications. Angiographic follow-up was obtained in seven patients (9 stents) at a mean of 26.1±25.9 months (range, 2–66) after stenting. One patient was noted to have in-stent re-stenosis of 60%, but without any new neurologic events by 26-month clinical follow-up. Telephone or clinical follow-up was achieved in all 10 patients at a mean of 60.7±16.5 months after stenting. No patient had recurrent stroke. No patient had late in-stent thrombosis. Two patients experienced recurrent TIA at 36 months and 9 months, respectively, after stenting. Repeat angiography in those two demonstrated no re-stenosis. Both patients were taking aspirin and clopidogrel at the time of recurrent symptoms. All patients were independent at follow-up. Conclusion: The safety and long-term efficacy of DES in preventing recurrent stroke in symptomatic patients with high-grade intracranial arterial stenosis who are refractory to medical management is promising and should encourage further study of that intervention for that patient subgroup. Competing interests: R Gottumukkala: None. Y Kadkhodayan: None. A Mazumdar: None. C Moran: EV3, Stryker, Codman. C Derdeyn: W.L Gore and Associates. nFocus, Pulse therapeutics. D Cross: None.